Problematika Pengajuan Izin Cuti Notaris dan Pengangkatan Notaris Pengganti - Raissa Maxentia; H. Eman Suparman; Nanda Anisa Lubis (Jurnal Hukum Lex Generalis, 2026)
In carrying out their duties, notaries have the right to take leave as employees. This study examines the legal certainty and responsibilities of notaries regarding notarial leave permits and the appointment of replacement notaries. From a normative juridical perspective, this study shows that submitting a notarial leave permit as regulated in Article 25 of the Notary Law is part of an effort to ensure legal certainty and the continuity of notarial services. Violations of the obligation to obtain leave permits, including leaving the office without permission or continuing to make deeds during leave, result in administrative sanctions up to dismissal and the downgrading of the deed to an unsigned deed. In addition, notaries who violate this obligation can be held legally accountable and are required to compensate for any losses incurred, so compliance with the leave mechanism is an important aspect in maintaining legal certainty and protection.